Total humerus replacement for osteosarcoma with proximal part of humerus: a case report - Yoshida, Yukihiro (BioMed Central, 2012)
Incisional biopsy and intramedullary pinning were performed for pathological fracture associated with a malignant bone tumor of the proximal humerus. Osteosarcoma, for which preoperative chemotherapy had been performed, was confirmed by postoperative pathological examination. To achieve wide resection and acquire a safe resected margin, total humerus replacement was performed, and the whole humerus was reconstructed using the Howmedica Modular Reconstruction system. The patient resumed normal activities, although mild contracture of the elbow joint remains 8 years after surgery.